2013
DOI: 10.1016/j.mam.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The maternal to zygotic transition in mammals

Abstract: Prior to activation of the embryonic genome, the initiating events of mammalian development are under maternal control and include fertilization, the block to polyspermy and processing sperm DNA. Following gamete union, the transcriptionally inert sperm DNA is repackaged into the male pronucleus which fuses with the female pronucleus to form a 1-cell zygote. Embryonic transcription begins during the maternal to zygotic transfer of control in directing development. This transition occurs at species-specific tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
155
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 229 publications
2
155
0
1
Order By: Relevance
“…Although the exact identity of most of these factors remains a mystery, they are nevertheless instrumental in preparing the oocyte for the egg to embryo transition. [1][2][3][4][5] The presence and correct storage of these maternal factors is crucial for embryonic genome activation (EGA) which needs to occur for proper embryonic development. 6,7 During this transition, mRNAs are released, translated, and the resulting proteins, along with other stored maternal factors, are targeted to the nucleus in a regulated fashion where they then orchestrate the nuclear reprogramming events leading to the EGA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact identity of most of these factors remains a mystery, they are nevertheless instrumental in preparing the oocyte for the egg to embryo transition. [1][2][3][4][5] The presence and correct storage of these maternal factors is crucial for embryonic genome activation (EGA) which needs to occur for proper embryonic development. 6,7 During this transition, mRNAs are released, translated, and the resulting proteins, along with other stored maternal factors, are targeted to the nucleus in a regulated fashion where they then orchestrate the nuclear reprogramming events leading to the EGA.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 During this transition, mRNAs are released, translated, and the resulting proteins, along with other stored maternal factors, are targeted to the nucleus in a regulated fashion where they then orchestrate the nuclear reprogramming events leading to the EGA. 2,[8][9][10][11] It has been reported that 75-80% of ribosomes in the mouse oocytes are not incorporated into polysomes at ovulation and do not engage in protein synthesis in vitro. 12,13 Interestingly, previous studies have suggested that these inactive ribosomes are embedded in the oocyte cytoplasmic lattices (CPLs), a highly abundant structure that has been well-described in the literature but remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,10 For this purpose, one has to take into account that mammalian species differ in the timing of major embryonic gene activation. 2 In rabbit embryos this event apparently starts, like in bovine embryos, at the 8-cell stage. In a previous study of in vivo derived and cloned rabbit embryos from our group, only occasional nuclei recorded at this stage showed the peripheral chromatin arrangement phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…1 This critical event occurs at species-specific times after one or several rounds of blastomere cleavage. 2 In bovine embryos major embryonic genome activation takes place at the 8-cell stage, where the largest proportion of genes becomes active during preimplantation development. 3 Some genes, however, are already activated earlier during minor genome activation.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm passes its paternal genetic and epigenetic information to the embryo via the male pronucleus. After gamete fusion, the protamines must be removed, which is linked with a widespread and rapid DNA demethylation process, which suggests that the paternal epigenome has an important role during embryonic development [1,2]. This DNA demethylation takes place before the first round of replication, which indicates an active process [3].…”
Section: Introductionmentioning
confidence: 99%